Test of CP Invariance in vector-boson fusion production of the Higgs boson using the Optimal Observable method in the ditau decay channel with the ATLAS detector - Aad, G. (2016)
A test of CP invariance in Higgs boson production via vector-boson fusion using the method of the Optimal Observable is presented. The analysis exploits the decay mode of the Higgs boson into a pair of τ leptons and is based on 20.3 fb−1 of proton–proton collision data at √ s = 8 TeV collected by the ATLAS experiment at the LHC. Contributions from CPviolating interactions between the Higgs boson and electroweak gauge bosons are described in an effective field theory framework, in which the strength of CP violation is governed by a single parameter d˜. The mean values and distributions of CP-odd observables agree with the expectation in the Standard Model and show no sign of CP violation. The CP-mixing parameter d˜ is constrained to the interval [−0.11, 0.05] at 68% confidence level, consistent with the Standard Model expectation of d˜ = 0.